Revision of margins under frozen section in oral cancer: a retrospective study of involved margins in pT1 and pT2 oral cancers. Issue 9 (November 2015) - Gokavarapu, Sandhya; Rao, L.M. Chandrasekhara; Mahajan, Munish; Parvataneni, Nagendra; Raju, K.V.V.N.; Chander, Ravi
Abstract: Operative assessment of the resection margins by frozen section is routine in many hospitals, but the usefulness of the technique relies on its sensitivity, specificity, sampling errors, and errors associated with relocation of involved margins. Its usefulness is indicated by assessment of overall survival and locoregional recurrence in patients whose margins were initially involved but were successfully revised after frozen section compared with those of the patients whose initially-involved margins were not revised. Patients with consecutive primary pT1, pT2 oral squamous cell carcinoma in whom initial resection resulted in involved margins were selected from the patients treated during the period January 2010 to December 2011 at a tertiary cancer hospital in India. The outcome of patients whose revision of margins after frozen section was successful was compared with that of patients who had "false negative" results after frozen section. Sixty-eight patients had involved margins after initial resection, of whom 42 (62%) had successful revision after frozen section (clear margins group). The remaining 26 patients (38%) had "false negative" results on frozen section, and had no further revision (invaded margins group). Local recurrence was more common in the invaded margins group, although not significantly so in this short retrospective series (p=0.08). The risk of death was greater in patients with local recurrence, hazard ratio (HR) 4.74 (95% CI 1.79 to 12.61, p=0.002). However, overall survival (p=0.073), incidence of locoregional recurrence (p=0.59) and neck recurrence (p=1.0), did not differ significantly between the groups.